Prevalence of metabolic syndrome and its association with physical activity among adults in Kampung Chengal Lempong - Phyu, Htike Myat (2013)
Objective Metabolic syndrome (MetS) is a cluster of risk factors associated with morbidity and mortality of cardiovascular diseases. This study was conducted to measure the prevalence of MetS and its association with physical activity among adults in Kampung Chengal Lempong, Kuantan. Methods A cross-sectional study was conducted from 1st October until 1st November 2012. Houses in the village were selected by simple random sampling and adults between 18-64 years old in the houses were interviewed. Physical activity level was determined by Global Physical Activity Questionnaire-Malay Version (GPAQ-M). Blood pressure, waist circumference, and blood investigation were done to diagnose MetS according to Modified National Cholesterol Education Programme’s Adult Treatment Panel III (NCEP ATP III) criteria definition. Data were analysed by chi-square and multiple logistic regression tests. Results Out of 108 respondents, 23 (21.3%) had MetS, of which 87% were physically inactive. After adjusting the data for other risk factors (age, gender, smoking, monthly household income and body mass index), it was found that there is no significant association between MetS and physical activity. Conclusion Prevalence of MetS was lower when compared to a 2011 Malaysian nationwide survey. The association between MetS with physical activity was statistically insignificant.